Prevalence, symptoms, and associated factors of chronic constipation among older adults in North-East of Peninsular Malaysia - Abdul Wahab, Patimah; Mohd Yusoff, Dariah; Abdul Kadir, Azidah; Ali, Siti Hawa; Lee, Yeong Yeh (SAGE, 2021)
This study aimed to determine the prevalence, symptoms, and associated factors of chronic constipation among older adults in the North-East of Peninsular Malaysia. A cross-sectional study was conducted among older patients from four health clinics. A total of 400 older patients participated, with a mean age of 68.7 (SD = 6.4) years. The prevalence of chronic constipation was 14.8%. The highest symptom reported was the inability to pass stool (98.3%). Chronic constipation was significantly associated with older age (OR = 2.97; 95% CI [1.17, 7.54]; p = .022), inadequate plain water intake per day (OR = 2.13; 95% CI [1.13, 4.02]; p = .020), hypertension (OR = 2.22; 95% CI [1.07, 4.61]; p = .033), and hyperlipidemia (OR = 2.52; 95% CI [1.24, 5.11]; p = .010). Identification of chronic constipation should be done as part of routine clinic visits, especially for older patients with cardiovascular disease.